2012
DOI: 10.1007/s00894-012-1360-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of beryllium bonds; a QTAIM study

Abstract: The nature of beryllium bonds formed between BeX2 (X is H, F and Cl) and some Lewis bases have been investigated. The distribution of the Laplacian of electron density shows that there is a region of charge depletion around the Be atom, which, according to Laplacian complementary principal, can interact with a region of charge concentration of an atom in the base and form a beryllium bond. The molecular graphs of the investigated complexes indicate that beryllium in BeH2 and BeF2 can form “beryllium bonds” wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…Studies of beryllium bonds in complexes between BeH 2 and HArF 13 have been reported, and the results analyzed using the QTAIM methodology. 14 Previously, we investigated the beryllium bonds formed between the acids BeX 2 , for X = H, F, Cl, and OH, and a variety of Lewis bases. 15 These bonds have bond critical points, and in some cases slightly negative energy densities, indicating partial covalent character.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of beryllium bonds in complexes between BeH 2 and HArF 13 have been reported, and the results analyzed using the QTAIM methodology. 14 Previously, we investigated the beryllium bonds formed between the acids BeX 2 , for X = H, F, Cl, and OH, and a variety of Lewis bases. 15 These bonds have bond critical points, and in some cases slightly negative energy densities, indicating partial covalent character.…”
Section: Introductionmentioning
confidence: 99%
“…. .Y [63][64][65]. The Be atom, like H and Li, is also highly electropositive and therefore the interaction energies of beryllium bonds tend to have a substantial electrostatic component and are generally comparable in strength to very strong hydrogen bonds.…”
Section: Beryllium Bondingmentioning
confidence: 98%
“…Electronic charge may also be transferred into the A-Be/A -Be antibonding orbital (σ * A-Be/A -Be ). The shift in charge densities greatly increase the covalent character of beryllium bonds [63,64] and may result in relatively high ρ bcp for these bonds compared to their hydrogen-bonded analogues [63].…”
Section: Beryllium Bondingmentioning
confidence: 98%
“…Some of these reported studies on beryllium bonding are in Refs. [11][12][13][14][15][16][17][18][19]. A particularly interesting finding is that beryllium bonds can change a weak halogen bond into a stronger interaction, with the cooperative effect of the beryllium bond increasing with the basicity of the Lewis base [17].…”
Section: Introductionmentioning
confidence: 98%
“…In some respects it is similar to hydrogen bonding -some researchers justifiably find merit in considering the Be atom as a hydrogen atom with a core of electrons [11,12]. It is however a stronger intermolecular interaction, exhibiting partial covalent character in some instances [11].…”
Section: Introductionmentioning
confidence: 99%